2002
DOI: 10.1007/s00213-002-1217-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine, sleep loss, and stress on cognitive performance and mood during U.S. Navy SEAL training

Abstract: Even in the most adverse circumstances, moderate doses of caffeine can improve cognitive function, including vigilance, learning, memory, and mood state. When cognitive performance is critical and must be maintained during exposure to severe stress, administration of caffeine may provide a significant advantage. A dose of 200 mg appears to be optimal under such conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
302
4
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(347 citation statements)
references
References 37 publications
18
302
4
11
Order By: Relevance
“…Correspondingly, Lieberman et al (2002) found that following sleep deprivation, executive and reaction time measures were all impaired. Compared to the pre-sleepdeprivation baseline, nearly all measures were degraded: participants' hits on a vigilance task decreased by almost half whereas reaction time increased; all visual reaction time measures were impaired, and spatial working memory was also significantly impaired (correct responses decreased, reaction time increased and timeout errors increased).…”
Section: Introductionmentioning
confidence: 91%
“…Correspondingly, Lieberman et al (2002) found that following sleep deprivation, executive and reaction time measures were all impaired. Compared to the pre-sleepdeprivation baseline, nearly all measures were degraded: participants' hits on a vigilance task decreased by almost half whereas reaction time increased; all visual reaction time measures were impaired, and spatial working memory was also significantly impaired (correct responses decreased, reaction time increased and timeout errors increased).…”
Section: Introductionmentioning
confidence: 91%
“…The military deployment cycle increases the likelihood of servicemembers enduring psychological and physical harm, as well as suffering degradation in cognitive functioning (Marx et al 2009;Tanielian et al 2008;Vasterling et al 2006). In the months leading up to their deployment to a combat zone, servicemembers engage in mission-critical operational field training and Bstress-inoculation^training, which have been linked to degradation in cognitive performance (Lieberman et al 2002b(Lieberman et al , 2005Morgan et al 2006). Thus, the very cognitive faculties necessary for troops to best meet the challenges of combat may be compromised even before they are deployed.…”
mentioning
confidence: 99%
“…Current research is more supportive of the benefits of caffeine. For example, it was found that moderate doses of caffeine improved cognitive function, including vigilance, memory, learning, and mood state among US Navy SEAL trainees under limited sleep conditions (Lieberman, Tharion, Shukitt-Hale, Speckman, & Tulley, 2002).…”
Section: Current Statusmentioning
confidence: 99%